Reducing the digital divide as a goal for a knowledge-based economy: Lessons learned from the European Union - Tislenko, Maria; Petrović, Marko D.; Massarova, Alena; Radovanović, Milan M.; Potapenko, Maria (Indonesian Journal of Geography, 2025)
The research examines the European Union’s (EU’s) policy to boost digitalization and reduce the digital divide. It involves seven strategic documents and three funding programs to evaluate their impact on building a knowledge-based economy in EU member states. It aims to identify connections between the EU’s digital divide reduction policy and the path toward a knowledge economy. The analysis includes comparative, correlation, and regression analyses of the strategic planning documents, funding, and statistical data. It reveals a discrepancy between the EU’s digital divide reduction policy and the goals of a knowledge-based economy. The implementation is hindered by inadequate and uneven funding, as well as the declarative nature of the goals outlined in the strategic documents. Furthermore, the correlation analysis of the Digital Economy and Society Index (DESI), the Global Knowledge Index (GKI), and proxy variables reveals significant relationships between digital transformation, a knowledge-based economy, and overall socio-economic development. The outcome revealed that the EU’s policy lacks synchronization in reducing digital divides using financial instruments, which hampers the efficiency of transitioning to a digital economy and impedes the potential for technological and socio-economic development in EU countries. Received: 2025-06-06 Revised: 2025-12-16  Accepted: 2025-12-31 Published: 2025-12-31